A Meta‐Analysis of Trabecular Bone Score in Fracture Risk Prediction and Its Relationship to FRAX. (19th November 2015) - McCloskey, Eugene V; Odén, Anders; Harvey, Nicholas C; Leslie, William D; Hans, Didier; Johansson, Helena; Barkmann, Reinhard; Boutroy, Stephanie; Brown, Jacques; Chapurlat, Roland; Elders, Petra JM; Fujita, Yuki; et al.
ABSTRACT: Trabecular bone score (TBS) is a gray‐level textural index of bone microarchitecture derived from lumbar spine dual‐energy X‐ray absorptiometry (DXA) images. TBS is a bone mineral density (BMD)‐independent predictor of fracture risk. The objective of this meta‐analysis was to determine whether TBS predicted fracture risk independently of FRAX probability and to examine their combined performance by adjusting the FRAX probability for TBS. We utilized individual‐level data from 17, 809 men and women in 14 prospective population‐based cohorts. Baseline evaluation included TBS and the FRAX risk variables, and outcomes during follow‐up (mean 6.7 years) comprised major osteoporotic fractures. The association between TBS, FRAX probabilities, and the risk of fracture was examined using an extension of the Poisson regression model in each cohort and for each sex and expressed as the gradient of risk (GR; hazard ratio per 1 SD change in risk variable in direction of increased risk). FRAX probabilities were adjusted for TBS using an adjustment factor derived from an independent cohort (the Manitoba Bone Density Cohort). Overall, the GR of TBS for major osteoporotic fracture was 1.44 (95% confidence interval [CI] 1.35–1.53) when adjusted for age and time since baseline and was similar in men and women ( p > 0.10). When additionally adjusted for FRAX 10‐year probability of major osteoporotic fracture, TBS remained a significant, independent predictor for fracture (GR = 1.32, 95% CI 1.24–1.41). The adjustment of FRAX probability for TBS resulted in a small increase in the GR (1.76, 95% CI 1.65–1.87 versus 1.70, 95% CI 1.60–1.81). A smaller change in GR for hip fracture was observed (FRAX hip fracture probability GR 2.25 vs. 2.22). TBS is a significant predictor of fracture risk independently of FRAX. The findings support the use of TBS as a potential adjustment for FRAX probability, though the impact of the adjustment remains to be determined in the context of clinical assessment guidelines. © 2015 American Society for Bone and Mineral Research.